Precision Surgery for Pheochromocytomas and Paragangliomas - Wiseman, Douglas; Lakis, Mustapha El; Nilubol, Naris (Hormone and Metabolic Research, 2019)
Since Felix Fränkel’s account of pheochromocytoma in 1886, great discoveries and vast advancements in the diagnosis, genetics, anatomical and functional imaging techniques, and surgical management of pheochromcytoma and paraganglioma (P-PGL) have been made. The improved insight in the pathophysiology of P-PGL and more accurate detection methods enable physicians to tailor the treatment plan to an individual based on the genetic profile and tumor behavior. This review will cover briefly the clinical features, diagnosis, genetic mutations, and imaging modalities that are used to guide current surgical management of these rare and interesting endocrinopathies.
Keywords: pheochromocytoma; paraganglioma; precision surgery; clusters; biochemical phenotypes; genetic testing; anatomic and functional imaging